Synergistic roles of Wnt modulators R-spondin2 and R-spondin3 in craniofacial morphogenesis and dental development - Nora Alhazmi (Nature Portfolio, 2021)
Abstract Wnt signaling plays a critical role in craniofacial patterning, as well as tooth and bone development. Rspo2 and Rspo3 are key regulators of Wnt signaling. However, their coordinated function and relative requirement in craniofacial development and odontogensis are poorly understood. We showed that in zebrafish rspo2 and rspo3 are both expressed in osteoprogenitors in the embryonic craniofacial skeleton. This is in contrast to mouse development, where Rspo3 is expressed in osteoprogenitors while Rspo2 expression is not observed. In zebrafish, rspo2 and rspo3 are broadly expressed in the pulp, odontoblasts and epithelial crypts. However, in the developing molars of the mouse, Rspo3 is largely expressed in the dental follicle and alveolar mesenchyme while Rspo2 expression is restricted to the tooth germ. While Rspo3 ablation in the mouse is embryonic lethal, zebrafish rspo3-/- mutants are viable with modest decrease in Meckel’s cartilage rostral length. However, compound disruption of rspo3 and rspo2 revealed synergistic roles of these genes in cartilage morphogenesis, fin development, and pharyngeal tooth development. Adult rspo3 −/− zebrafish mutants exhibit a dysmorphic cranial skeleton and decreased average tooth number. This study highlights the differential functions of Rspo2 and Rspo3 in dentocranial morphogenesis in zebrafish and in mouse.